More Efficiency of Solar Energy System in Libya Using Artificial Intelligence (Fuzzy Logic Control) (Aintelia Science Notes, 2022)
Recently, the entire world is facing the problem of energy. One method of harnessing incident solar radiation to generate power without releasing carbon dioxide (CO2) is solar photovoltaic (PV) energy. So, it's critical to give a broad summary of Libya's current energy production situation. The purpose of this paper was to shed light on the energy issues that the Libyan state is now dealing with, as well as the potential for diagnosing and outlining a plan for developing and locating solutions that make the most of solar radiation. The majority of the nation's energy consumption—roughly 36%—comes from residential building loads. This paper focus to how solar PV is currently being used in Libya and suggests using artificial intelligence as a controller to boost the effectiveness of the solar energy system. Using Fuzzy Logic controller (FLC) to collect the largest amount of energy which can reach 95% or more, by control tracking the radiation of the solar, cleaning and control on the temperature solar board.
Keywords: Solar PV applications; Renewable energy in Libya; Fuzzy Logic control (FLC); Sun tracker; Solar panels Cleaning System; Temperature